Temperature studies of optical absorption in the sandwich structure based on (Ag₃AsS₃)₀.₆(As₂S₃)₀.₄ thin film and gold nanoparticles - Studenyak, I.P.; Molnar, Z.R.; Kutsyk, M.M.; Izai, V.Yu.; Kranjcec, M.; Kokenyesi, S. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2018)
(Ag₃AsS₃)₀.₆(As₂S₃)₀.₄ thin films deposited using the thermal evaporation technique onto glass substrates previously covered with layers of gold nanoparticles were studied. Optical transmission spectra of the sandwich structure were studied within the temperature range 77–300 K. The absorption spectra in the region of its exponential behaviour were analyzed, the dispersion dependences of refractive index as well as the temperature dependences of the energy pseudogap and Urbach energy were investigated. The disordering processes in the sandwich structure were discussed. The comparative analyses of optical parameters in a single (Ag₃AsS₃)₀.₆(As₂S₃)₀.₄ layer and in the sandwich structure were performed.